El FMLN y las memorias de la guerra civil salvadoreña - López Bernal, Carlos Gregorio (2017)
This article studies the construction of the memories of the Salvadoran civil war (1981-1992) from a historical perspective. It is proposed that war is remembered from the specifcity of the experience of the different leftist actors, which gives rise to multiple memories, of which some examples are given. It is not possible to understand the memories of the civil war without considering the experiences of organization and struggle of the 1970s, which have been absorbed by the offcial memory of the Farabundo Martí National Liberation Front (FMLN), now political party. By appropriating these memories, the FMLN makes a political use of the past in terms of its current political project that is far from the revolutionary project.